Comparison of mechanical performance between friction-stir spot welded and adhesive bonded joints - Reis, Paulo N. B. (2020)
The main goal of this study is to compare the morphology and mechanical strength of friction stir spot welded (FSSW) joints and adhesive bonded stepped joints. The welded joints were produced by friction stir spot welding, while the adhesive bonded ones used an Araldite 420 A/B adhesive. All joints were subjected to morphology and microstructure analyses, microhardness tests, tensile-shear tests and local strain analyses. It was possible to conclude that the welded joints have higher strength than adhesive-bonded joints. However, this difference is insignificant, around 5%, which is covered by the standard deviation. Therefore, FSSW technique proves to be an alternative to adhesive bonded joints, offering the same strength. Nevertheless, the friction stir spot welded induces isolated connection points, which are responsible for stress concentrations.